STRUCTURE OF COMMITMENT OF CUSTOMER AND THEIR RELATIONSHIP WITH THE SATISFACTION - Salvador Ferrer, Carmen María (Anales de Psicología / Annals of Psychology, 2005)
The present paper intends to validate the organizational commitment´s customer construct as a multidimensional concept. The starting point are the tree theoretical perspectives traditionally use to study the commitment: affective, normative and continuance. Also, the influence of the commitment was analyzed in the user’s satisfaction. In this study, a questionnaire a rating -scale with six questions were use to survey 223 customers of services non educational university students. Results show that the traditional perspectives (affective, normative and calculated) are important for the analysis of the commitment. Also, the data reflect that these categories can be organized in two macrodimensions (ethics and calculated), which influence significantly in the customer’s satisfaction. Finally, the implications of these results are discussed and directions for future research are suggested.